SOCIAL MEDIA LEARNING PLATFORMS (SMLPs) AS A PERFORMANCE ENHANCER AMONG SENIOR SECONDARY SCHOOL SCIENCE STUDENTS. - Ajayi, Peter Oladeji; Ajayi, Folasayo (Advances in Social Sciences Research Journal, 2020)
The study examined the effects of Social Media Learning Platforms (SMLPs) on secondary school students’ performance in Science in Nigeria. It also investigated the rate of use of social media for the purpose of education or otherwise among science students in Secondary schools in Nigeria. The study was a quasi-experimental of pre-test, post-test research design. The sample for the study was 80 Senior Secondary School two students, selected from two schools in Ondo state, South West, Nigeria. Purposive sampling technique was adopted in the selection of the schools and classes for the study. The choice of the sampling technique used was to ensure that the schools and classes selected have access to cell phones and internet facilities during school period and that the classes are science based. The instruments used for the study were Social Media Students Participation Rating Scale (SMSPRS), Social Media Students’ Performance Test in Science (SMSPTS), Social Media Students’ Questionnaire (SMSQ). Validity and Reliability of the instruments were ensured and determined. Data collated were analyzed using frequency count, mean, standard deviation and t-test. The outcome of the analysis revealed that 98% of the students’ sampled do not use social media for educative learning purposes but for entertainment and socialization. Students exposed to the use of social media platform with conventional teaching-learning method participated better in lessons and performs better in the subject than their counterparts with no use of social media platform